The effect of perceived parental attitude score on symptoms of bipolar disorder and schizophrenia - Yazla, Ece; Aydinoglu, Unsal; Ozalp, Elvan (The European Research Journal, 2023)
Objectives: We aimed to investigate the effect of perceived parental attitudes on the symptoms of these diseases in patients with schizophrenia and bipolar disorder (BD) and to compare the perceived parental attitudes between these two disorders. Methods: This cross-sectional study was conducted between August 2020 and August 2021 at a university hospital in Turkey. Fifty-two patients with BD and 50 patients with schizophrenia in remission, aged 16-50 years, who met the respective diagnostic criteria defined by the Diagnostic and Statistical Manual of Mental Disorder-5 were included in the study. Results: The mean age of patients with BD was 38.90 ±1 0.95 years, while it was 39.08 ± 11.51 years for those with schizophrenia. Females comprised 65.38% (n = 34) of the BD group and 78.00% (n = 39) of the schizophrenia group. Our results showed that the severity of various negative schizophrenia symptoms increased with higher levels of perceived parental libertarian attitude. In addition, the severity of delusion, which is one of the positive symptoms of schizophrenia, was found to increase with lower perceived parental interest. We did not find a significant relationship between the severity of mania and depression symptoms and perceived parental attitudes. Conclusions: In addition to supporting previously reported relationships of various factors and schizophrenia and BD, our results suggest that the increase in the level of liberality of parents has a negative impact on the negative symptoms of schizophrenia. In addition, the decrease in the level of interest of parents towards their children exacerbates delusion symptoms.